Analisis Kesediaan Membayar (Willingness To Pay) Terhadap Pengelolaan Sampah di Pasar Tugu dan Faktor-Faktor yang Mempengaruhi.docx - Neli Aida; Ratih, Arivina; Astuti, Sari (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2021)
Continuous population growth will lead to high human activities that affect the increase in public consumption. Increased consumption and community activities will increase the waste generated from daily life. This study aims to (1) examine the characteristics of the Tugu market traders, (2) estimate the value of the merchants' willingness to pay to improve waste management and (3) analyze the variables that influence the willingness to pay for waste management towards improving waste management in Monument Market. This study uses data obtained from questionnaire data. The analysis used is the contingent valuation method (CVM) and logistic regression with SPSS ver. 25. The results show that (1) the characteristics of traders in Tugu Market are mostly traders with high school education, income of Rp. 100,000-Rp. 250,000, the duration of trading is more than 10 years, the status of the place of trade is rent. (2) the average WTP of kiosk traders is Rp. 4,063.00. los/amparan traders are Rp. 3,078.00 and street vendors Rp. 3,545.00 and a total WTP of Rp 224,668.00, (3) the factors that influence the willingness to pay are education, length of trade and status of the place of trade.Key Words: SFA, Panel Data, Efficiency